Fear of Hypoglycemia among Diabetics in the Middle East: A Systematic Review and Meta-analysis - Hazim M. Bajri,; Sultan Alessa,; Adel Alshehri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The Middle East and North Africa face high diabetes rates, contributing significantly to global diabetes burdens. Addressing diabetes management, including awareness, early diagnosis, and complication prevention, is a critical health priority due to its expanding burden. The psychosocial aspect of diabetes, particularly fear of hypoglycemia (FOH), affects patient outcomes by discouraging physical activity, reducing quality of life, and impacting treatment adherence and glycemic control. Evidence on FOH and its effects on diabetes management in the Middle East is limited, prompting a systematic literature review to synthesize available data. Methods: A systematic search on PubMed, Web of Science (WOS), Scopus, and Cochrane Library was conducted from inception till May 5, 2024. Relevant studies were obtained and evaluated for inclusion, and their data were extracted. Our primary outcome was fear of hypoglycemia (FOH) as measured by the hypoglycemia fear survey (HFS). The R language was used to pool the means of HFS scores, and the narrative approach was used to synthesize evidence for other outcomes. Results: Fourteen studies, comprising 4,869 participants, were included in the analysis. The overall pooled mean HFS among diabetic patients in the Middle East was 24.13 (95% CI: 13.92 to 34.34), indicating a moderate level of FOH. Younger age, longer duration of diabetes, treatment modality, and history of hypoglycemia were found to influence FOH levels. Patients with higher FOH levels reported lower treatment satisfaction, impaired emotional well-being, social interactions, and overall life satisfaction. Conclusion: Diabetes patients in the Middle East have moderate levels of FOH. However, FOH negatively affected patients' quality of life in multiple aspects and treatment outcomes. Future well-designed research is warranted.